Impact of epidemic infectious disease and death on stock returns: Evidences from Asian stock markets with COVID-19 - Sapkota, Shiba Prasad (Contemporary Research: An Interdisciplinary Academic Journal, 2020)
The causal comparative study regarding impact of pandemic COVID-19 on stock return revealed that the changes on daily confirmed new cases have been severely inflected stock returns in overall as well as cross-over the industries. Whereas, the influence of death form COVID-19 found negative but mostly insignificant. The categorical variables size of economy, geographical area, regulations, and country specific impact have been found very low. The empirical evidences were examined using causality test with the backing of regression. The study period has covered 20thJanuary to 30thMay 2020, considering eight nations: China, India, Israel, Japan, Korea Republic, Malaysia, Saudi Arabia, and United Arab Emirates, as samples.